Quality characteristics of snap beans in the developing world - Cajiao V., César Hernando (International Center for Tropical Agriculture, 1990)
Pod quality requirements in snap beans vary from region to region. Characteristics related to pod shape, length, color and fiber content, among others, determine the degree to which snap beans are accepted by consumers and processors. The snap bean program at CIAT screens accessions from the germplasm collection and breeding lines for these characteristics, as well as adaptation and disease susceptibility. Information about the quality requirements of some Latin American countries is provided. Research on environmental and agronomic factors affecting snap bean pod quality is also discussed. (AS)